A report on anomalies of digastric muscle - Holibková, Alžběta; Machálek, Libor (Acta Universitatis Palackianae Olomucensis Facultatis medicae. Biomedical papers, 1999)
The anterior belly of the digastric muscle varies greatly in shape and size. In this report, two cases of anomalies in the digastric muscle found in necropsy material belonging to the Institute of Anatomy are described. In the first case, we found a bilateral anomaly--a lateral widening of the muscle belly as an adaptation; this was shown by separation of the anterior muscle belly of digastric muscle into a medical and lateral head. The latter of which passing through the intermediate tendon and fixing partially on the hyoid bone. In the second case, a bilateral asymmetrical anomaly of the anterior belly was described. This involved the separation of the anterior belly into medial and lateral parts and the occurrence of accessory bundles; these bundles run from the left part of the mandible to the intermediate tendon of the right side of digastric muscle and to the hyoid bone.
Keywords: lidé středního věku; mužské pohlaví; Facial Muscles; lidé; obličejové svaly; Middle Aged; Humans; Male